A China-developed adenovirus vector-based COVID-19 vaccine: review of the development and application of Ad5-nCov - Shen-Yu Wang; Wen-Qing Liu; Yu-Qing Li; Jing-Xin Li; Feng-Cai Zhu (Taylor & Francis Group, 2023)
Introduction The global spread of COVID-19 has prompted the development of vaccines. A recombinant adenovirus type-5 vectored COVID-19 vaccine (Ad5-nCoV) developed by Chinese scientists has been authorized for use as a prime and booster dose in China and several other countries. Areas covered We searched published articles as of 4 May 2023, on PubMed using keywords related to Adenovirus vector, vaccine, and SARS-CoV-2. We reported the progress and outcomes of Ad5-nCov, including vaccine efficacy, safety, immunogenicity based on pre-clinical trials, clinical trials, and real-world studies for primary and booster doses. Expert opinion Ad5-nCoV is a significant advancement in Chinese vaccine development technology. Evidence from clinical trials and real-world studies has demonstrated well-tolerated, highly immunogenic, and efficacy of Ad5-nCoV in preventing severe/critical COVID-19. Aerosolized Ad5-nCoV, given via a novel route, could elicit mucosal immunity and improve the vaccine efficacy, enhance the production capacity and availability, and reduce the potential negative impact of preexisting antibodies. However, additional research is necessary to evaluate the long-term safety and immunogenicity of Ad5-nCoV, its efficacy against emerging variants, its effectiveness in a real-world context of hybrid immunity, and its cost-effectiveness, particularly with respect to aerosolized Ad5-nCoV.